Antipsychotic agents deteriorate brain and retinal function in schizophrenia patients with combined auditory and visual hallucinations: A pilot study and secondary follow‐up study. Issue 6 (14th April 2020) - Zhuo, Chuanjun; Xiao, Bo; Chen, Ce; Jiang, Deguo; Li, Gongying; Ma, Xiaoyan; Li, Ranli; Wang, Lina; Xu, Yong; Zhou, Chunhua; Lin, Xiaodong
Abstract: Introduction: Schizophrenia patients often experience auditory hallucinations (AHs) and visual hallucinations (VHs). However, the degree and type of brain and retinal alterations associated with combined AHs and VHs in schizophrenia patients remain unknown. There is an urgent need for a study that investigates the trajectory of brain and retinal alterations in patients with first‐episode untreated schizophrenia accompanied by combined AHs and VHs (FUSCHAV). Methods: FUSCHAV patients ( n = 120), divided into four groups according to AH and VH symptom severity (severe AHs combined with severe VHs [FUSCHSASV, 20 patients]; middle‐to‐moderate AHs combined with severe VHs [FUSCHMASV, 23 patients]; severe AHs combined with middle‐to‐moderate VHs [FUSCHSAMV, 28 patients]; and middle‐to‐moderate AHs combined with middle‐to‐moderate VHs [FUSCHMAMV, 26 patients]), were compared to healthy controls ( n = 30). Gray matter volume (GMV) was adopted for brain structural alteration assessment. Total retinal thickness was adopted as a measure of retinal thickness impairment. Results: In the pilot study, the rate of GMV reduction showed an inverted U‐shaped pattern across the different FUSCHAV patient groups according to AH and VH severity. The degree of retinal impairment remained stable across the groups. More notably, in the secondary follow‐up study, we observed that, after 6 months of treatment with antipsychotic agents, all the GMV reduction‐related differences across the different patient groups disappeared, and both GMV and retinal thickness demonstrated a tendency to deteriorate. Conclusions: These findings indicate the need for heightened alertness on brain and retinal impairments in patients with FUSCHAV. Further deteriorations induced by antipsychotic agent treatment should be monitored in clinical practice. Abstract : (1) GMV reduction and gFCD increases in the frontal–parietal lobule of FUSCHAV patients demonstrate an inverted U‐shape pattern according to differences in AH and VH severity, indicating functional compensation correlated with volume reduction. (2) There appears to be reciprocal deterioration in auditory and visual disturbances among FUSCHAV patients as observed through both brain and retinal abberations. (3) Although brain alterations in FUSCHAV patients differ with degree of AH and VH severity, retinal impairment remains constant among FUSCHAV groups.